A great reckoning [compact disc, unabridged] - Penny, Louise (Penny, Louise. Three Pines mystery., 2016)
"When an intricate old map is found stuffed into the walls of the bistro in Three Pines, it at first seems no more than a curiosity. But the closer the villagers look, the stranger it becomes. Given to Armand Gamache as a gift the first day of his new job, the map eventually leads him to shattering secrets. To an old friend and older adversary. It leads to the former Chief of Homicide for the Súreté du Québec to places even he is afraid to go. But must. And there he finds four young cadets in the Súreté Academy and a dead professor. And, with the body, a copy of the old, odd map. Everywhere Gamache turns, he sees Amelia Choquet, one of the cadets. Tattooed and pierced. Guarded and angry. Amelia is more likely to be found on the other side of a police lineup. And yet she is in the academy. A protégée of the murdered professor. For both Amelia Choquet and Armand Gamache, the time has come for a great reckoning."--